Management by roaming among kindergarten principals (Journal of the College of Basic Education, 2023)
Summary of the research:The objective of the current research is to identify the management by roaming among kindergarten principals, and to identify the significance of differences in the management by roaming among kindergarten principals according to specialization and length of service. 2004), as the researcher prepared (35) paragraphs distributed on (7) dimensions (stimulating and stimulating interest and conversation, intelligent listening, intelligent use of questions and dialogue, removing fear and dread, sharing others in work problems, development and creativity, new ideas). The apparent validity of the management scale by roaming and the consistency of its paragraphs, and calculating its stability by the re-test method, as the stability coefficient reached (0.82). The research data is processed by statistical means that are compatible with the nature and objectives of the current research. The researcher reached the following results: The kindergarten principals have a roaming administration. Specialization and length of service.Research extracted from a master's thesis